Peran Emas dalam Menjaga Kestabilan Nilai Tukar dan Mengurangi Inflasi Perspektif Ekonomi Islam - Fadhli Suko Wiryanto; Faiz Andreas Fawwaz; Muhammad Alif Shafwan; Elca Vebi Anggelyani; Wafa Az zahra (Journal of Economic and Business Advancement, 2025)
This study aims to analyze the role of gold in maintaining exchange rate stability and reducing inflation from an Islamic economic perspective, given the increasing exchange rate volatility and inflationary pressures on the fiat money-based monetary system. The study focuses on the characteristics of gold as an asset with intrinsic value that has hedging capabilities and its relevance to Islamic monetary principles. The research method used is descriptive with a literature study approach, utilizing secondary data in the form of official reports from the Central Statistics Agency, data on gold prices, exchange rates, inflation, as well as scientific literature and related regulations. The results and discussion show that gold has a positive correlation as a monetary stabilization instrument, especially in mitigating the effects of exchange rate depreciation and inflation, due to its limited supply and global acceptance. In Islamic economics, gold is considered capable of maintaining the fairness of money value, protecting purchasing power, and supporting sustainable economic stability. The conclusion of the study confirms that strengthening the role of gold as a monetary and Islamic financial instrument has the potential to be a strategic alternative in strengthening national monetary resilience and reducing inflation vulnerability.